The midnight star - Lu, Marie, 1984- (2016)
"With new threats looming, Adelina's forced to revisit old wounds, putting not only herself at risk, but every Elite and the very world they live in"--
Keywords: Supernatural -- Fiction; Ability -- Fiction; Adventure and adventurers -- Fiction; Secret societies -- Fiction